HARMONI KEBERAGAMAAN: ANALISIS KEBERAGAMAAN INKLUSIF DALAM BHAGAWADGĪTĀ DAN IMPLIKASINYA PADA KEHIDUPAN MANUSIA DALAM KONTEKS GLOBAL - Arya Juni Arta, I Gede; Darsana, I Made (Fakultas Dharma Duta dan Brahma Widya, 2023)
This research is a literature study or library research. The method of data analysis uses a hermeneutical approach conducted reflectively through philosophy. This study articulates that inclusive religiosity is crucial in the current global era to create a peaceful, secure, and harmonious life. Inclusive religiosity views all religions as having the same position, truth, and purpose, originating from the Supreme God. Plurality is a necessity as different paths to reach the same truth, as each seeker of truth has unique characteristics. Based on the research findings, it is revealed that inclusive religiosity in the Bhagavadgītā has at least three implications: first, it opens up a space for interreligious dialogue grounded in awareness of the Nirguṇa and Saguṇa Brahman dimensions. The consciousness between these two opens up an inclusive space with a shared understanding that each religion has its own characteristics and conceptualizations that cannot be forced into uniformity, but rather the substance of truth in each religion is eternal (directed towards the One God). Second, it builds a shared consciousness (global ethics) through collective ethical awareness of love and non-violence, crucially established to address the current crises of justice and peace. Third, it strengthens unity among humans through brotherhood irrespective of race and religion, as a unity of the family of the universe.